Charge-neutral epitaxial graphene on 6H–SiC(0001) via FeSi intercalation. (January 2020) - Luo, Xingyun; Liang, Guojun; Sun, Xiucai; Li, Yanlu; Yu, Fapeng; Wei, Lei; Cheng, Xiufeng; Sun, Li; Zhao, Xian
Abstract: Graphene grown epitaxially on SiC(0001) substrates always exhibits n -type doping due to the coupling interaction between the substrate and graphene. The electronic properties of epitaxial graphene are thus impaired relative to those of free-standing graphene, limiting its potential in device applications. In this work, by using first-principles calculations, we show that charge neutrality can be achieved by growing an FeSi intercalation layer between the SiC substrate and the buffer carbon layer. The formation of an atomic Si layer between FeSi and the buffer carbon layer prevents electron transfer to the subsequent graphene layer. The subsequently grown graphene therefore displays the electronic characteristics of quasi-free-standing graphene with charge neutrality. The calculated surface energy of the FeSi-intercalated structure shows considerable stability compared to elemental Fe- and H-intercalated structures over a wide range of temperature and pressure. This will promote the practical application of FeSi-intercalated epitaxial graphene on SiC(0001) at high temperature as a core element of microelectronic devices. Graphical abstract: Image 1